Accelerated Silverlight 3 - Scanlon, Jeff; Ghoda, Ashish (Apress : Imprint: Apress, 2009)
Accelerated Silverlight 3 teaches you how to get up to speed with the latest version of Silverlight quickly and efficiently. The book assumes you're already comfortable with the basics of .NET coding and with WPF and builds on your existing knowledge to make your journey to Silverlight 3 proficiency as quick and painless as possible. Where coding techniques are similar to other, more established, areas of .NET, the text says so. Likewise, where there's a syntax or conceptual "gotcha" that you're existing coding habits will walk you into, the text points that out, too. This book provides you with fast-track coverage of all the most important elements of the Silverlight 3 technology ranging from XAML to standard controls, from dealing with media to networking, from testing to deployment. It concludes with a pair of fully worked sample applications for you to follow through, because nothing reinforces your understanding of how concepts fit together as much as looking at finished code. It is assumed that readers are already be comfortable with the workings of the .NET framework. Knowledge of Expression Blend is useful, but not mandatory: you'll learn the Blend techniques that you need to know as you go through the book. By the end, you will have followed a sound, concise, path to mastery of Silverlight 3.